(untitled) (Bangladesh Journal of Otorhinolaryngology, 2015)
Objectives: To evaluate morbidity of different modalities of treatment in advanced carcinoma larynx (stage III and IV). Methods: It was a cross sectional study conducted among selected 70 patients of advanced carcinoma larynx treated by different modalities of treatment from April 2009 to April 2010 in different tertiary hospitals in Dhaka. Results:The age of the patients ranged from 30 to 79 years (mean ± SD = 54±10.94), maximum age incidence 5th decade. Almost all were male, habituated in betel nut and leaves chewing and smoking. Mostly (60%) from poor socioeconomic group. 70% cases were supraglottic and 30% cases were glottic carcinoma. Nature of lesion was exophytic 71.43% and ulcerative 28.57%. 22.86% had neck node metastasis. Histopathologically 60% were moderately differentiated and grade II squamous cell carcinoma (SCC). In the total laryngectomy patient pharyngocuteneous fistula (30%), wound infection (10%), haematoma (10%), stomal recurrence (10%), stenosis is tracheostomy (10%), recurrent chest infection (10%) and pharyngeal stenosis (10%) were the morbidities. Mucositis or painful erythematous reaction in larynx and pharynx (95%), periconditis (2.5%), dryness of mouth and throat (100%), loss of test (100%), subcutaneous fibrosis (32.5%), nausea vomiting, skin rashes and alopecia (100%) were the morbidities of chemoradiotherapy and radiotherapy. After analysis the major and minor morbidities of different, modalities of treatment there was no significant (p > 0.05) difference among those modalities. Conclusion: The difference between the morbidity of single modality and combined modalities had not significant. So the combined modalities approach may be advocated for the treatment of advanced carcinoma larynx where required. DOI: http://dx.doi.org/10.3329/bjo.v20i2.22021 Bangladesh J Otorhinolaryngol; October 2014; 20(2): 66-74